Temporal Bone Cancer (Springer International Publishing, 2018)
This volume comprehensively reviews the current literature on temporal bone cancer and the multidisciplinary approaches used to managing these rare tumors. The text will review important medical issues as they specifically relate to temporal bone cancer such as advanced imaging, pathologic classification, skull base surgery, plastic reconstructive surgery, and advances in osseointegrated implants for hearing restoration. Additional chapters are dedicated to the evaluation and management, diagnostic radiology, surgical planning and techniques, radiotherapy, chemotherapy, and rehabilitation. An emphasis is placed on the multidisciplinary approach required for the optimal care of these rare tumors. Written by leaders in the field, Temporal Bone Cancer will be an invaluable resource for residents and fellows in Otolaryngology, Neurosurgery and Neurotology, and clinicians with interest in the primary tumors of the temporal bone. .